ANC-leaders at the ANC's 46th National Conference in Durban. In the middle (behind small microphone): chief Albert Luthuli (1959)
ANC-leaders at the ANC's 46th National Conference in Durban. In the middle (behind small microphone): chief Albert Luthuli.